Analisis Rasio Likuiditas, Rasio Aktivitas, Rasio Leverage, Dan Rasio Profitabilitas Pada Kinerja Keuangan Koperasi Jasa Keuangan Syari'ah Babussalam Sragen - Marsono, Andrian Tri; , Lukman Hakim, SE, M.Si (2016)
The objective of this study, namely: (1) To determine the financial performance of Shari'ah Financial Service Cooperative (KJKS) Babussalam Sragen the period 2012 to 2014 based on the liquidity ratios activity ratios, leverage ratios and profitability ratios. The location of this research is done in the Cooperative Financial Services Shari'ah (KJKS) Babussalam Sragen. This study is classified as a case study in the Cooperative Financial Services Shari'ah (KJKS) Babussalam Sragen. This means that the conclusions and implications of the results of the study only used for the object under study is the analysis of the financial performance KJKS Babussalam Sragen. Data collection techniques used by the author is the documentation. To determine the financial performance of cooperatives uses time series on the ratio. Test the hypothesis by using time series method. The conclusion of this study are: (1) Rated current ratio and quick ratio on the liquidity ratio has increased, demonstrating the ability KJKS Babussalam Sragen able to repay short-term obligations. (2) The ratio of activity was in good condition, the circumstances indicate that the KJKS Babussalam Sragen utilize all available resources in effective control. (3) Leverage Ratio for three years of decline, so that the Leverage Ratio KJKS Babussalam Sragen including unfavorable. (4) Values of profitability ratios well, it happens because KJKS Babussalam Sragen has been unable to cope with the magnitude of expenditure burdens, so that performance can be done less efficiently.